ANALISIS KINERJA LINGKUNGAN PERUSAHAAN BUMN DAN NON BUMN YANG TERDAFTAR DALAM INDEKS SRI KEHATI TAHUN 2010-2014 - WAHYUNINGTYAS, RETNO (Jurnal Akuntansi AKUNESA, 2016)
The purpose of this research is to explain CSR comparison report between state-owned and private company listed on SRI KEHATI indeks in 2010 until 2014. This research method is a descriptive six with 30 company objects. The company that became the object is state-owned and private company consistently followed PROPER and SRI KEHATI indeks in 2010 until 2014. The research result showed that the environmental performance between state-owned and private companies in 2010 until 2014 are differed significantly.